THE EFFECT OF PREGNANT MOTHER’S BEHAVIOR IN THE PRE-PURCHASE STAGE TOWARDS THE SELECTION OF BIRTHPLACE - Rika Aprilia; Novita Aulia Effendy; Feni Choirun Nisa; Ratna Dwi Wulandari (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2019)
Background: A preliminary study at Mother and Child Hospital of Nyai Ageng Pinatih, Gresik, showed a gap between the number of pregnant women conducting antenatal examinations and the number of deliveries at the hospital in 2011. The number of pregnant women visits for antenatal care was relatively high. It is known that the average number of pregnant mothers giving birth at Mother and Child Hospital of Nyai Ageng Pinatih in 2011 was only 53.85%.  Aims: This study aimed to analyse the effect of maternal behaviour on the pre-purchasing stage during pregnancy in choosing a birth location.Methods: This research was an analytical study with a cross sectional design. The population of this study was 235 mothers who completed the antenatal care at Mother and Child Hospital of Nyai Ageng Pinatih and were predicted to give birth around March to May 2012. The sample size was 75 people determined by using a cluster sampling method. Each independent variable was tested by identifying the influence on the choice of birth location by using univariate logistic regression with α value of <0.05.  Results: The results of this study indicated that maternal behaviour in the pre-purchasing stage of delivery services consists of 3 stages (identification of needs, information seeking, and evaluation of alternatives) that influence the choice of birth place by pregnant mothers. It showed that the pre- purchasing stage has an impact on the choice of delivery place.Conclusions: The mother's behavior at the pre-purchasing stage during pregnancy influences the choice of delivery place inside and outside Mother and Child Hospital of Nyai Ageng Pinatih. Providing information about maternity care and delivery services can promote services provided at the hospital. The hospital should provide brochures about available services, post posters about health service options available, and promote delivery services conducted by obstetricians or midwives as an alternative delivery service. Keywords: Mother’s behaviour, Pre-purchasing stage, Selection of delivery location.